Oligarki dan Elit Politik pada Pilkada 2020: Sebuah Ulasan - Faedlulloh, Dodi; Sulistiowati, Rahayu; Apandi, Apandi; Karmilasari, Vina (Journal of Political Issues, 2023)
This article analyzes the political practices of oligarchy and elite politics in the context of the 2020 local elections in Indonesia. Despite the high number of Covid-19 cases, Indonesia continued to hold simultaneous local elections, making the regional elections even more controversial. The significance of this research lies in understanding the existence of oligarchic and elite political practices in Indonesia's election administration. The article employs a qualitative method using desk study by analyzing relevant literature to answer the research problem. The novelty of this research is in providing an analysis of the political practices of oligarchy and elite politics in the context of the 2020 local election. The findings indicate that the 2020 local elections were characterized by the re-strengthening of kinship politics, high single candidates, and the involvement of actors with oligarchic interests. These are indications that oligarchic and elite politics are returning to dominate election administration in Indonesia. The implications of this research are essential for understanding the challenges of democratization in Indonesia and the need to strengthen democratic institutions and practices.